Exposure to the One-Child Policy and Fertility among Chinese Immigrants to the US - Siyuan Lin; Laura M. Argys; Susan L. Averett (Institute of Labor Economics (IZA), 2023)
We examine whether women exposed to China's one-child policy (OCP) change their fertility decisions when they migrate to a country without fertility restrictions. Using American Community Survey data (2010–2020), we compare the childbearing decisions of Chinese-born women with varying degrees of exposure before migrating to the US to each other and a control group of other Asian immigrants. We find that Chinese women aged 35-45 exposed to the OCP for a longer duration have significantly fewer children than women who were not exposed to the OCP. These findings are robust to several specification checks.
Keywords: F22; I15; J13; N35; 330; fertility; one-child policy; immigrants; China